2014
DOI: 10.1016/j.bbrc.2014.08.069
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitinase Leon/USP5 regulates ubiquitin homeostasis during Drosophila development

Abstract: Ubiquitination and the reverse process deubiquitination regulate protein stability and function during animal development. The Drosophila USP5 homolog Leon functions as other family members of unconventional deubiquitinases, disassembling free, substrate-unconjugated polyubiquitin chains to replenish the pool of mono-ubiquitin, and maintaining cellular ubiquitin homeostasis. However, the significance of Leon/USP5 in animal development is still unexplored. In this study, we generated leon mutants to show that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 28 publications
(46 reference statements)
2
34
0
Order By: Relevance
“…2A). Death at third instar larval stage is the same as observed with DmUSP5 null mutation (20). The level of knockdown obtained by the ubiquitous sqh-Gal4 driver was determined through qRT-PCR and is shown in Fig.…”
Section: Drosophila and Human Usp5 Disassemble Unanchoredmentioning
confidence: 96%
See 3 more Smart Citations
“…2A). Death at third instar larval stage is the same as observed with DmUSP5 null mutation (20). The level of knockdown obtained by the ubiquitous sqh-Gal4 driver was determined through qRT-PCR and is shown in Fig.…”
Section: Drosophila and Human Usp5 Disassemble Unanchoredmentioning
confidence: 96%
“…DmUSP5 is expressed throughout the fly (20); therefore, we targeted this protease in the whole organism by using the ubiquitous drivers sqh-Gal4, actin-Gal4, and da-Gal4 with similar results. We used three different RNAi lines specific for DmUSP5 that target different sites of its mRNA.…”
Section: Drosophila and Human Usp5 Disassemble Unanchoredmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the loss-of-function mutation in the Rpn10/p54 polyubiquitin receptor subunit of the proteasome [16,17] and in one of the DUB genes in Drosophila, Usp5 [18,19], leads to disruption of ubiquitin equilibrium and an excessive accumulation of free polyubiquitins and polyubiquitylated proteins. To quantitate these changes, we applied the immunoblot-based ubiquitin quantification assay to determine the steady-state distribution of ubiquitin forms in animals with impaired Rpn10/p54 and Usp5 functions and compared them to wild type data.…”
Section: Changes In Ubiquitin Forms Via Loss Of Rpn10/p54 and Usp5 Fumentioning
confidence: 99%